Method for preparing wear-resistant coating on titanium-based surface through micro-arc oxidation
By using acidic electrolyte containing phosphoric acid, oxalic acid and other components on the titanium-based surface for microarc oxalization, combined with the constant current to constant pressure mode, the lack of wear resistance and biocompatibility of titanium-based implants is solved, and efficient resistance is achieved Grinding coating preparation improves implant stability and biocompatibility.
Patent Information
- Application Number
- CN202411270258.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-11
- Publication Date
- 2024-12-13
Smart Images

Figure CN119121352A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of biomedical materials and relates to a method for preparing a wear-resistant coating by micro-arc oxidation of a titanium-based material in an acidic electrolyte. Background Art
[0002] Titanium and titanium alloys have become the preferred materials in the field of dental implants. However, in the complex human environment, the wear resistance and corrosion resistance of titanium and titanium alloy implant surfaces still need to be further improved. Metal surface modification technology is one of the most effective methods. Titanium and titanium alloy implants can be improved through various surface modification technologies, such as coating, physical and chemical treatment, to improve their integration with bone tissue, reduce the risk of infection, and improve clinical success rate.
[0003] The existing dental implant surface modification technologies on the market mainly include sandblasting and etching (SLA) technology, anodizing technology and micro-arc oxidation technology. For example, Straumann mainly uses sandblasting and etching technology, Nobel mainly uses anodizing technology, and most domestic manufacturers also use SLA technology in large quantities. Sandblasting and etching technology can easily lead to uneven surface roughness, especially on workpieces with complex shapes, it is difficult to accurately control the surface quality, and this technology has limited improvement on surface wear resistance; the oxide layer formed by anodizing is usually thinner and has lower hardness. At present, domestic implant brands lack competitiveness compared with imported products, and the performance of the sandblasting and etching technology used has reached a bottleneck. Micro-arc oxidation technology forms a porous structure with biological activity on the surface of titanium and titanium alloys. The coating is generally an oxide ceramic coating, which not only improves its biocompatibility and wear resistance, but also can be used as a drug loading system to deliver corresponding drugs, increase the functionality of the coating, enhance its antibacterial properties and clinical application effects. It is a technology with broad application prospects in implant surface treatment.
[0004] For implants, surface biocompatibility, bone integration, wear resistance and corrosion resistance are equally important. Micro-arc oxidation technology can meet all of the above requirements at the same time. The wear debris generated after implantation will have a certain impact on the surrounding tissues, such as causing an inflammatory response in the tissues around the implant, leading to peri-implant mucositis or peri-implantitis; the wear debris may cause physical damage to the surrounding tissues; increase the risk of infection; long-term wear debris stimulation may lead to alveolar bone resorption and affect the stability of the implant. Therefore, the use of micro-arc oxidation technology can simultaneously improve the biocompatibility, bone integration, and wear resistance of the surface of pure titanium and titanium alloys, and has great application value. However, in the currently available information, there are no reports on how to improve the wear resistance of titanium-based micro-arc oxidation coatings. Summary of the invention
[0005] Aiming at the deficiencies of the prior art, the present invention designs and develops a method for preparing a wear-resistant coating on a titanium-based surface by adopting micro-arc oxidation.
[0006] The present invention solves the problem that the existing coating with good wear resistance needs to be prepared by adding a hard phase or a soft phase, resulting in a complex coating composition. At the same time, the present invention also solves the problem that the products obtained by the prior art are difficult to prepare a coating with both wear resistance and surface bioactivity.
[0007] The present invention discloses a method for preparing a wear-resistant coating on a titanium substrate surface by using micro-arc oxidation, comprising the following steps: using a titanium substrate with a clean and dry surface as a treatment object, using the treatment object as an anode and stainless steel as a cathode, placing the cathode and the anode in a micro-arc oxidation solution and performing micro-arc oxidation to prepare a wear-resistant coating on the titanium substrate surface;
[0008] The micro-arc oxidation liquid comprises phosphoric acid, oxalic acid, hydrogen peroxide, glycerol and additives; in the micro-arc oxidation liquid, the concentration of phosphoric acid is 0.1-0.5 mol / L, preferably 0.2-0.3 mol / L, the concentration of oxalic acid is 0.5-1.5 mol / L, preferably 0.85-1 mol / L, the concentration of hydrogen peroxide is 0.5-1 mol / L, preferably 0.8-1.2 mol / L, and the concentration of glycerol is 0.1-0.2 mol / L, preferably 0.14-0.16 mol / L; the additive is selected from at least one of 1,2-cyclohexanediaminetetraacetic acid, sulfuric acid, hydrochloric acid, formic acid, nitric acid, and acetic acid; among the additives of the micro-arc oxidation liquid, the concentration of any one additive is 0.01-1 mol / L.
[0009] As a further preference, the electrolyte ratio is: phosphoric acid concentration is 0.3 mol / L, oxalic acid concentration is 1 mol / L, glycerol concentration is 0.15 mol / L, hydrogen peroxide concentration is 1 mol / L; and additives include 1,2-cyclohexanediaminetetraacetic acid 0.05 mol / L, sulfuric acid 0.4 mol / L, and formic acid 0.05 mol / L.
[0010] As one of the further preferred schemes, the ratio of the electrolyte is: the concentration of phosphoric acid is 0.25 mol / L, the concentration of oxalic acid is 0.5 mol / L, the concentration of glycerol is 0.15 mol / L, the concentration of hydrogen peroxide is 1.2 mol / L; and the additives are 1,2-cyclohexanediaminetetraacetic acid 0.05 mol / L, sulfuric acid 0.5 mol / L, and acetic acid 0.1 mol / L.
[0011] As one of the further preferred schemes, the ratio of the electrolyte is: the concentration of phosphoric acid is 0.25 mol / L, the concentration of oxalic acid is 0.5 mol / L, the concentration of glycerol is 0.15 mol / L, the concentration of hydrogen peroxide is 1.2 mol / L; and the additives are 1,2-cyclohexanediaminetetraacetic acid 0.05 mol / L, sulfuric acid 0.5 mol / L, formic acid 0.1 mol / L, and acetic acid 0.1 mol / L.
[0012] As one of the further preferred schemes, the ratio of the electrolyte is: the concentration of phosphoric acid is 0.25 mol / L, the concentration of oxalic acid is 0.5 mol / L, the concentration of glycerol is 0.15 mol / L, the concentration of hydrogen peroxide is 1.2 mol / L; and the additives are 1,2-cyclohexanediaminetetraacetic acid 0.05 mol / L, sulfuric acid 0.2 mol / L, formic acid 0.05 mol / L, and acetic acid 0.05 mol / L.
[0013] When used in industry, the titanium substrate is cut (including wire cutting) according to the set size, and a small hole is reserved, and then the surface is pretreated to obtain a sample with a clean and dry surface. In the present invention, the purpose of pretreating the surface of pure titanium and titanium alloy samples is mainly to remove organic matter, oil stains and oxide layers. In the specific operation, the following process can be selected: ultrasonically treat in acetone and alcohol for 3-8 minutes each to remove impurities such as organic solvents on the surface, and then air-dry. Then polish with 80#, 320#, 800#, and 1200# sandpaper step by step, ultrasonically treat in alcohol and deionized water for 5 minutes, and air-dry for use.
[0014] In the present invention, the titanium substrate is clamped by a titanium wire clamp and connected to the positive electrode of the power supply, and the distance from the cathode is 30-100 mm. The micro-arc oxidation electrolyte is between the positive electrode and the negative electrode. The cathode can be a stainless steel electrolytic cell. The titanium substrate is pure titanium or titanium alloy.
[0015] The present invention discloses a method for preparing a wear-resistant coating on a titanium-based surface by micro-arc oxidation, wherein the power supply mode used in the micro-arc oxidation is a constant current to constant voltage mode. The constant current to constant voltage mode is: the initial control is a constant current mode, and when the voltage reaches a specified value, the constant current mode is changed to a constant voltage mode.
[0016] The micro-arc oxidation electrical parameters include:
[0017] The forward current is 0.1-2.5A, preferably 1-2A, and more preferably 1.5-2A;
[0018] The positive voltage is 160-400V, preferably 200-350V, and more preferably 240-310V. When used in industry, 240-260V, 258-280V, 280-305V, etc. can be selected.
[0019] The negative voltage is 0-15V, preferably 4-11V, and more preferably 5-10V;
[0020] The frequency is 0-150 Hz, preferably 80-120 Hz, and more preferably 95-105 Hz.
[0021] In the present invention, the current of the forward constant current set is first energized, and when the voltage reaches the set value, micro-arc oxidation is performed in a constant voltage manner. If the forward current is set to a fixed value of 0.1-2.5A (preferably 1-2A) in the early stage, when the forward voltage of the energized value reaches a fixed value B of 160-400V (preferably 200-350V), the constant current mode is changed into a constant voltage mode-that is, the forward voltage is controlled to be B value for constant voltage micro-arc oxidation. Under the ordinary constant voltage mode, the micro-arc oxidation is within tens of seconds after startup, and the current can even reach more than 10A, and the excessive current will affect the uniformity and compactness of the early coating, and then affect the coating performance. And adopting the constant current to constant voltage mode, the voltage growth rate in the early stage of micro-arc oxidation can be controlled. In the early stage of micro-arc oxidation, the titanium substrate surface can be processed for a period of time under uniform and appropriate current to obtain a more dense and uniform coating with a certain thickness.
[0022] The invention discloses a method for preparing a wear-resistant coating on a titanium-based surface by micro-arc oxidation. The micro-arc oxidation reaction time is 5-20 minutes and the temperature is 20-40°C.
[0023] In the present invention, the samples obtained after the treatment by micro-arc oxidation technology are ultrasonically cleaned with deionized water and anhydrous ethanol, respectively, and then air-dried in the air. Preferred solution: the samples obtained after the treatment by micro-arc oxidation technology are soaked in hot water for about 10-20 minutes, the hot water temperature is 40-90°C, preferably 60-80°C, and then ultrasonically cleaned with deionized water and anhydrous ethanol, and then air-dried in the air. This step is conducive to the closure of small pores in the flat area of the coating, and improves the density and corrosion resistance of the coating.
[0024] The present invention generates an oxide coating on the surface of a substrate, wherein the surface of the oxide coating is distributed with circular raised crater-shaped holes or raised groove-shaped holes, wherein some craters are connected, the area around the raised portion is relatively flat, and there are some small pores in the flat area around the raised portion, the pore diameter of the raised holes is 0.8-3 microns, the pore diameter of the small pores in the flat area is 0.1-0.8 microns, the coating thickness is 2-15 microns, and the coating components are mainly Ti, P, and O.
[0025] The porosity of the oxide ceramic is less than or equal to 20%, preferably 2%-20%.
[0026] After the optimized design of the present invention, the friction coefficient of the coating is 0.12-0.15, and the wear rate is less than 9.2×10- 7 mm 3 ·N -1 ·m -1 .
[0027] Beneficial Effects
[0028] The electrolyte used in the present invention contains an appropriate amount of oxalic acid, hydrogen peroxide, glycerol and additives. The role of an appropriate amount of oxalic acid in micro-arc oxidation is mainly reflected in its influence on the generation of oxides in the micro-arc oxidation process. Adding an appropriate amount of oxalic acid in the micro-arc oxidation electrolyte can increase the growth rate and density of the film layer, thereby improving the performance of the film layer, and may also affect the structure and performance of the micro-arc oxidation film layer, such as improving the corrosion resistance or wear resistance of the film layer. The role of hydrogen peroxide (hydrogen peroxide) in micro-arc oxidation of pure titanium and titanium alloys is mainly reflected in that as a part of the electrolyte, it can improve the quality and performance of the oxide film layer. Hydrogen peroxide, as an oxidant, can participate in the electrochemical reaction during the micro-arc oxidation process. The addition of an appropriate amount of hydrogen peroxide helps to form a more uniform and dense oxide film, thereby improving the corrosion resistance, wear resistance and insulation performance of the film layer. In addition, an appropriate amount of hydrogen peroxide can also affect the microstructure and phase composition of the oxide film, further optimizing the performance of the film layer. By adjusting the hydrogen peroxide content in the electrolyte, the redox reaction during the discharge process can be controlled, thereby affecting the growth rate and quality of the film layer. An appropriate amount of hydrogen peroxide can promote the formation of TiO2 nanocrystals in the film layer and improve the hardness and wear resistance of the film layer. In addition, the addition of hydrogen peroxide can also improve the energy consumption problem in the micro-arc oxidation process. By adjusting the conductivity of the solution, the arc starting voltage can be reduced, effectively reducing the power and energy consumption per unit area, which helps to reduce production costs. The application of 1,2-cyclohexanediaminetetraacetic acid in medicine is mainly as a chelating agent, which can form complexes with metal ions. These complexes participate in the formation of the film layer during the micro-arc oxidation process, thereby affecting the chemical composition and phase structure of the film layer. Its addition will change the conductivity and electrochemical properties of the electrolyte, thereby affecting the stability of micro-arc discharge and the growth rate of the film layer, and help to enhance the bonding force between the film layer and the metal substrate, and improve the adhesion of the film layer.
[0029] The coating provided by the present invention is generated on the surface of the substrate by an in-situ growth method. The inner layer structure is dense, so that the implant has good corrosion resistance and wear resistance. The main component is titanium dioxide (mainly rutile phase and anatase phase); the outer layer structure is uniformly crater-shaped, and the holes are interconnected. The coating has high bonding strength and structural stability with the substrate, is not easy to peel off during use, and has good mechanical properties.
[0030] The present invention provides a relatively accurate parameter range for the micro-arc oxidation process of pure titanium and titanium alloys, such as voltage, current frequency, duty cycle and reaction time, which can achieve fine control of the micro-arc oxidation process and ensure the uniformity and consistency of the coating. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] Figure 1 The surface morphology (a) and cross-sectional morphology (b) of the coating prepared by micro-arc oxidation of pure titanium in an acidic electrolyte in Comparative Example 1 of the present invention are shown.
[0032] Figure 2 Surface morphology of the coating prepared by micro-arc oxidation of pure titanium in an acidic electrolyte according to Examples 1(a) and 2(b) of the present invention.
[0033] Figure 3 It is the surface morphology (a) and cross-sectional morphology (b) of the coating prepared by micro-arc oxidation of pure titanium in acidic electrolyte in comparative example 2 of the present invention.
[0034] Figure 4 This is a surface morphology of a coating prepared by micro-arc oxidation of pure titanium in an acidic electrolyte according to Example 3 of the present invention.
[0035] Figure 5 It is the surface morphology of the coating prepared by micro-arc oxidation of pure titanium in acidic electrolyte in Examples 4(a) and 5(b) of the present invention.
[0036] Figure 6 It is a cross-sectional morphology diagram of a coating prepared by micro-arc oxidation of pure titanium in an acidic electrolyte according to Example 5 of the present invention.
[0037] Figure 7 It is a cross-sectional morphology diagram of a coating prepared by micro-arc oxidation of pure titanium in an acidic electrolyte according to Example 6 of the present invention.
[0038] Figure 8 This is a graph of surface element contents of a coating prepared by micro-arc oxidation of pure titanium in an acidic electrolyte according to Example 5 of the present invention.
[0039] Fig. 9 It is a schematic diagram of the friction coefficient of the coating prepared by micro-arc oxidation of pure titanium or titanium alloy in acidic electrolyte according to Comparative Examples 1-2 and Examples 1-6 of the present invention. DETAILED DESCRIPTION
[0040] The present invention designs and develops a method for preparing a wear-resistant coating on a titanium-based surface by micro-arc oxidation. The present invention uses micro-arc oxidation to generate a wear-resistant coating in an acidic electrolyte, including electrolyte composition, electrical parameters and the following steps.
[0041] Step 1, sample preparation and pretreatment: The titanium used in the present invention can be commercially available pure titanium or titanium alloy, or can be prepared by smelting and other methods. The ingot wire is cut into sample size, the sample is ultrasonically cleaned in acetone and anhydrous ethanol, and then polished step by step with 80#, 320#, 800#, and 1200# sandpaper, ultrasonically in anhydrous ethanol and deionized water for 5 minutes, and the sample is air-dried for use.
[0042] Step 2: prepare acidic electrolyte: the electrolyte concentration is based on the electrolyte ratio. The electrolyte capacity is 2L. Weigh or measure the corresponding solutes and add them into water. Then make the volume to 2L and stir evenly with a stirring device.
[0043] Step 3, micro-arc oxidation: insert a titanium wire with a diameter of 0.8-1mm into the small hole of the pretreated pure titanium or titanium alloy disc. The sample is hung on the titanium wire and placed in the electrolytic cell so that the sample is completely immersed in the electrolyte. The distance between the sample and the inner wall of the cathode stainless steel electrolytic cell is 30-100mm, and the titanium wire is connected to the positive pole of the power supply. Then set the micro-arc oxidation power supply parameters, including forward current, forward voltage, negative voltage, operating frequency, duty cycle, number of pulses and micro-arc oxidation time. During the experiment, use an electrolyte stirring device to stir to ensure that the electrolyte is uniform, and turn on the circulating cooling water device to control the electrolyte temperature below 40°C.
[0044] Step 4: After micro-arc oxidation, wait until the voltage drops to 0 V, remove the sample, and clean it with deionized water and anhydrous ethanol ultrasonically in turn, and then dry it in the air.
[0045] The electrolyte of the acidic electrolyte in step 2 includes phosphoric acid, oxalic acid, hydrogen peroxide and glycerol; the concentration of the phosphoric acid is 0.1-0.5 mol / L, the concentration of the oxalic acid is 0.5-1.5 mol / L, the concentration of the hydrogen peroxide is 0.5-1 mol / L, and the concentration of the glycerol is 0.1-0.2 mol / L. As a preferred embodiment, a small amount of additives and other additives can be added to the electrolyte, and the other additives are one or more of 1,2-cyclohexanediaminetetraacetic acid, sulfuric acid, hydrochloric acid, formic acid, nitric acid, and acetic acid. The concentration of a single additive in the other additives is 0.01-1 mol / L.
[0046] The electrical parameters of the micro-arc oxidation in step 3 include:
[0047] The forward current is 0.1-2.5A, preferably 1-2A, and more preferably 1.5-2A;
[0048] The positive voltage is 160-400V, preferably 200-350V, and more preferably 240-310V. When used in industry, 240-260V, 258-280V, 280-305V, etc. can be selected.
[0049] The negative voltage is 0-105V, preferably 54-11V, and more preferably 5-10V;
[0050] The frequency is 0-1050 Hz; preferably 80-120 Hz, and more preferably 95-105 Hz;
[0051] The micro-arc oxidation reaction time is 5-20 minutes and the temperature is 20-40°C.
[0052] Test Method
[0053] Surface / cross-section morphology and element content test: The surface and cross-section morphology of the samples were characterized using a scanning electron microscope (SEM, HeliosNanolab G3 UC, Czech Republic) equipped with EDS, secondary electron and backscattered electron mode, 20Kv.
[0054] Friction and wear test: The friction test was conducted using a ball-on-disc high-temperature friction and wear tester (Zhongke Kaihua HT-1000) with a load of 5N and a rotation speed of 120r / min. The grinding material used was a Si3N4 ceramic ball with a radius of 2mm, and the test lasted for 30min. After friction, the wear marks and the amount of wear were analyzed using SEM and an optical profiler (Veeco Metrology Inc WYKO NT9100, USA).
[0055] The pore size, porosity, coating thickness, etc. of the oxide film layer are calculated using Image Pro software.
[0056] Comparative Example 1
[0057] Step 1: Sample pretreatment
[0058] The TA2 disc was ultrasonically cleaned in acetone and anhydrous ethanol in turn, then polished with 80#, 320#, 800#, and 1200# sandpapers in stages, ultrasonically cleaned in anhydrous ethanol and deionized water for 5 minutes in turn, and air-dried for later use.
[0059] Step 2: Prepare acid electrolyte
[0060] The electrolyte ratio is: phosphoric acid concentration is 0.3 mol / L, oxalic acid concentration is 1.5 mol / L, and the volume is fixed to 2 L after mixing, and stirred evenly with a stirring device.
[0061] Step 3: Micro-arc oxidation
[0062] The electrical parameters were set as follows: positive voltage of 300 V, negative voltage of 5 V, frequency of 100 Hz, and micro-arc oxidation reaction time of 5 min, and temperature below 40 ° C. After micro-arc oxidation, the voltage dropped to 0 V, and the sample was removed and ultrasonically cleaned with deionized water and anhydrous ethanol in turn, and then dried in air.
[0063] The surface morphology (a) and cross-sectional morphology (b) of the micro-arc oxidation coating prepared by the above micro-arc oxidation technical parameters are shown in the attached Figure 1 The coating surface is porous and petal-like, with a pore size of 0.5-0.9 microns and a porosity of 5.62%. The coating cross section is thin, with a thickness of only 0.5-1.6 microns. The friction coefficient is 0.64 and the average wear rate is 1.06×10 - 3 mm 3 ·N -1 ·m -1 .
[0064] Example 1
[0065] Step 1: Sample pretreatment
[0066] The TA2 disc was ultrasonically cleaned in acetone and anhydrous ethanol in turn, then polished with 80#, 320#, 800#, and 1200# sandpapers in stages, ultrasonically cleaned in anhydrous ethanol and deionized water for 5 minutes in turn, and air-dried for later use.
[0067] Step 2: Prepare acid electrolyte
[0068] The electrolyte ratio is: phosphoric acid concentration is 0.3 mol / L, oxalic acid concentration is 1 mol / L, glycerol concentration is 0.15 mol / L, after mixing, the volume is fixed to 2 L, and stirred evenly with a stirring device.
[0069] Step 3: Micro-arc oxidation
[0070] The electrical parameters were set as follows: positive voltage of 300 V, negative voltage of 5 V, frequency of 100 Hz, and micro-arc oxidation reaction time of 5 min, and temperature below 40 ° C. After micro-arc oxidation, the voltage dropped to 0 V, and the sample was removed and ultrasonically cleaned with deionized water and anhydrous ethanol in turn, and then dried in air.
[0071] The coating prepared by the above-mentioned micro-arc oxidation technical parameters, the surface morphology and cross-sectional morphology of the coating of Example 1 are shown in the attached Figure 2 (a). The coating surface presents a grooved porous morphology with an average porosity of 7.26%. The coating thickness is 3-4 μm. The average friction coefficient is 0.62 and the average wear rate is 6.12×10 -4 mm 3 ·N -1 ·m-1 Compared with the previous exploration (such as comparative example 1), it is found that an appropriate amount of glycerol can not only reduce the wear rate of the coating, but also increase the thickness of the coating.
[0072] Example 2
[0073] Step 1: Sample pretreatment
[0074] The TA2 disc was ultrasonically cleaned in acetone and anhydrous ethanol in turn, then polished with 80#, 320#, 800#, and 1200# sandpapers in stages, ultrasonically cleaned in anhydrous ethanol and deionized water for 5 minutes in turn, and air-dried for later use.
[0075] Step 2: Prepare acid electrolyte
[0076] The electrolyte ratio is: phosphoric acid concentration is 0.3 mol / L, oxalic acid concentration is 1 mol / L, glycerol concentration is 0.15 mol / L, after mixing, the volume is fixed to 2 L, and stirred evenly with a stirring device.
[0077] Step 3: Micro-arc oxidation
[0078] Set the electrical parameters: the power mode is constant current to constant voltage mode, the forward current is set to 1A (when the voltage reaches 300V, it switches to constant voltage mode), the forward voltage is 300V, the negative voltage is 5V, the frequency is 100Hz; and the micro-arc oxidation reaction time is 5min, and the temperature is below 40°C. After micro-arc oxidation, wait until the voltage drops to 0V, remove the sample, and clean it with deionized water and anhydrous ethanol ultrasonically in turn, and then dry it in the air.
[0079] By adopting the constant current to constant voltage mode, the voltage growth rate in the early stage of micro-arc oxidation can be controlled. Figure 2 (b). The coating surface has protrusions, mainly groove-shaped porous morphology, with an average porosity of 5.39%. The coating thickness is 2-3 microns. The friction coefficient is 0.59 and the average wear rate is 9.05×10 -5 mm 3 ·N -1 ·m -1 .
[0080] Compared with the previous exploration (such as Example 1), it is found that the constant flow to constant pressure mode with appropriate parameters can further reduce the wear rate and porosity of the coating.
[0081] Comparative Example 2
[0082] Step 1: Sample pretreatment
[0083] The TA2 disc was ultrasonically cleaned in acetone and anhydrous ethanol in turn, then polished with 80#, 320#, 800#, and 1200# sandpapers in stages, ultrasonically cleaned in anhydrous ethanol and deionized water for 5 minutes in turn, and air-dried for later use.
[0084] Step 2: Prepare acid electrolyte
[0085] The electrolyte ratio is: phosphoric acid concentration is 0.3 mol / L, oxalic acid concentration is 1 mol / L, glycerol concentration is 0.15 mol / L, after mixing, the volume is fixed to 2 L, and stirred evenly with a stirring device.
[0086] Step 3: Micro-arc oxidation
[0087] Set the electrical parameters: the power mode is constant current to constant voltage mode, the forward current is set to 2A (when the voltage reaches 400V, it switches to constant voltage mode), the forward voltage is 400V, the negative voltage is 10V, the frequency is 100Hz; and the micro-arc oxidation reaction time is 20min, and the temperature is below 40°C. After micro-arc oxidation, wait until the voltage drops to 0V, remove the sample, and clean it with deionized water and anhydrous ethanol ultrasonically in turn, and then dry it in the air.
[0088] The surface morphology (a) and cross-sectional morphology (b) of the ceramic coating prepared by the above-mentioned micro-arc oxidation technical parameters are shown in the attached figure. Figure 3 Due to the high applied voltage, the surface morphology of the coating changes greatly and the porosity increases significantly. The coating thickness is up to 9.15 μm. The friction coefficient is 0.74 and the average wear rate is 7.29×10 -4 mm 3 ·N -1 ·m -1 .
[0089] Compared with the previous exploration (such as Example 2), it is found that the constant flow to constant pressure mode with inappropriate parameters not only does not reduce the wear rate of the coating, but may also have the opposite effect.
[0090] Example 3
[0091] Step 1: Sample pretreatment
[0092] The TA2 disc was ultrasonically cleaned in acetone and anhydrous ethanol in turn, then polished with 80#, 320#, 800#, and 1200# sandpapers in stages, ultrasonically cleaned in anhydrous ethanol and deionized water for 5 minutes in turn, and air-dried for later use.
[0093] Step 2: Prepare acid electrolyte
[0094] The electrolyte ratio is: phosphoric acid concentration is 0.3 mol / L, oxalic acid concentration is 1 mol / L, glycerol concentration is 0.15 mol / L, hydrogen peroxide concentration is 1 mol / L; and additives are 1,2-cyclohexanediaminetetraacetic acid 0.05 mol / L, sulfuric acid 0.4 mol / L, formic acid 0.05 mol / L. After mixing, the volume is fixed to 2 L and stirred evenly with a stirring device.
[0095] Step 3: Micro-arc oxidation
[0096] Set the electrical parameters: the power mode is constant current to constant voltage mode, the forward current is set to 2A (when the voltage reaches 250V, it switches to constant voltage mode), the forward voltage is 250V, the negative voltage is 5V, the frequency is 100Hz; and the micro-arc oxidation reaction time is 5min, and the temperature is below 40°C. After micro-arc oxidation, wait until the voltage drops to 0V, remove the sample, and clean it with deionized water and anhydrous ethanol ultrasonically in turn, and then dry it in the air.
[0097] The surface morphology of the micro-arc oxidation coating prepared by the above micro-arc oxidation technical parameters is similar to that of the Figure 4 (ac). Hydrogen peroxide, as an oxidant, helps to form a more uniform and dense oxide film, thereby improving the corrosion resistance and wear resistance of the film. In addition, an appropriate amount of hydrogen peroxide can also affect the microstructure and phase composition of the oxide film, further optimizing the performance of the film. An appropriate amount of hydrogen peroxide can promote the formation of TiO2 nanocrystals in the film, improving the hardness and wear resistance of the film. The surface presents a crater-like porous morphology with a pore size of 0.7-2 microns and a porosity of 7.15%. If you continue to zoom in, you can see that TiO2 nanocrystals are dispersed on the coating surface. The thickness is 4-6 microns. The friction coefficient is 0.15 and the wear rate is 9.13×10 - 7 mm 3 ·N -1 ·m -1 .
[0098] Example 4
[0099] Step 1: Sample pretreatment
[0100] The TA2 disc was ultrasonically cleaned in acetone and anhydrous ethanol in turn, then polished with 80#, 320#, 800#, and 1200# sandpapers in stages, ultrasonically cleaned in anhydrous ethanol and deionized water for 5 minutes in turn, and air-dried for later use.
[0101] Step 2: Prepare acid electrolyte
[0102] The electrolyte ratio is: phosphoric acid concentration is 0.25 mol / L, oxalic acid concentration is 0.5 mol / L, glycerol concentration is 0.15 mol / L, hydrogen peroxide concentration is 1.2 mol / L; and additives are 1,2-cyclohexanediaminetetraacetic acid 0.05 mol / L, sulfuric acid 0.5 mol / L, acetic acid 0.1 mol / L. After mixing, the volume is fixed to 2 L and stirred evenly with a stirring device.
[0103] Step 3: Micro-arc oxidation
[0104] Set the electrical parameters: the power mode is constant current to constant voltage mode, the forward current is set to 2A (when the voltage reaches 250V, it switches to constant voltage mode), the forward voltage is 250V, the negative voltage is 10V, the frequency is 100Hz; and the micro-arc oxidation reaction time is 10min, and the temperature is below 40°C. After micro-arc oxidation, wait until the voltage drops to 0V, remove the sample, and clean it with deionized water and anhydrous ethanol ultrasonically in turn, and then dry it in the air.
[0105] The surface morphology of the micro-arc oxidation coating prepared by the above micro-arc oxidation technical parameters is shown in the attached Figure 5 (a) There are pores with crater morphology and grooved pores. The porosity is reduced. The area outside the crater becomes flat, with only some small pores formed by small discharge channels. The thickness is not much different from that of Example 3. The friction coefficient is 0.12 and the wear rate is 6.69×10 - 7 mm 3 ·N -1 ·m -1 .
[0106] Example 5
[0107] Step 1: Sample pretreatment
[0108] The TA2 disc was ultrasonically cleaned in acetone and anhydrous ethanol in turn, then polished with 80#, 320#, 800#, and 1200# sandpapers in stages, ultrasonically cleaned in anhydrous ethanol and deionized water for 5 minutes in turn, and air-dried for later use.
[0109] Step 2: Prepare acid electrolyte
[0110] The electrolyte ratio is: phosphoric acid concentration is 0.25 mol / L, oxalic acid concentration is 0.5 mol / L, glycerol concentration is 0.15 mol / L, hydrogen peroxide concentration is 1.2 mol / L; and additives are 1,2-cyclohexanediaminetetraacetic acid 0.05 mol / L, sulfuric acid 0.5 mol / L, formic acid 0.1 mol / L, acetic acid 0.1 mol / L. After mixing, the volume is fixed to 2 L and stirred evenly with a stirring device.
[0111] Step 3: Micro-arc oxidation
[0112] Set the electrical parameters: the power mode is constant current to constant voltage mode, the forward current is set to 2A (when the voltage reaches 250V, it switches to constant voltage mode), the forward voltage is 250V, the negative voltage is 5V, the frequency is 100Hz; and the micro-arc oxidation reaction time is 5min, and the temperature is below 40℃. After micro-arc oxidation, the voltage drops to 0V, and the sample treated with micro-arc oxidation technology is soaked in hot water for about 15min, and the hot water temperature is 70℃. This step is conducive to the pore closure of the coating. Ultrasonic cleaning with deionized water and anhydrous ethanol in turn, and then dry in the air.
[0113] The surface morphology of the micro-arc oxidation coating prepared by the above micro-arc oxidation technical parameters is shown in the attached Figure 5 (b) The coating is smooth and uniform, showing a circular crater morphology, with some crater holes connected, a porosity of 5.02-5.74%, and a pore size of 1.5-1.8 microns. Example 5 Surface element content see attached Figure 8 The surface coating elements are only O, P, and Ti, with contents of 66.0%, 4.2%, and 29.8% (At.%) respectively. The cross-sectional morphology of Example 5 is shown in the attached Figure 6 , the crater section of the coating can be clearly seen, with a thickness of 5-6 μm. The friction coefficient is 0.14 and the wear rate is 7.23×10 -7 mm 3 ·N -1 ·m -1 .
[0114] Example 6
[0115] Step 1: Sample pretreatment
[0116] The TA2 disc was ultrasonically cleaned in acetone and anhydrous ethanol in turn, then polished with 80#, 320#, 800#, and 1200# sandpapers in stages, ultrasonically cleaned in anhydrous ethanol and deionized water for 5 minutes in turn, and air-dried for later use.
[0117] Step 2: Prepare acid electrolyte
[0118] The electrolyte ratio is: phosphoric acid concentration is 0.25 mol / L, oxalic acid concentration is 0.5 mol / L, glycerol concentration is 0.15 mol / L, hydrogen peroxide concentration is 1.2 mol / L; and additives are 1,2-cyclohexanediaminetetraacetic acid 0.05 mol / L, sulfuric acid 0.2 mol / L, formic acid 0.05 mol / L, acetic acid 0.05 mol / L. After mixing, the volume is fixed to 2 L and stirred evenly with a stirring device.
[0119] Step 3: Micro-arc oxidation
[0120] Set the electrical parameters: the power mode is constant current to constant voltage mode, the forward current is set to 2A (when the voltage reaches 300V, it switches to constant voltage mode), the forward voltage is 300V, the negative voltage is 5V, the frequency is 100Hz; and the micro-arc oxidation reaction time is 10min, and the temperature is below 40°C. After micro-arc oxidation, wait until the voltage drops to 0V, remove the sample, and clean it with deionized water and anhydrous ethanol ultrasonically in turn, and then dry it in the air.
[0121] The cross-sectional morphology of the micro-arc oxidation coating prepared using the above micro-arc oxidation technical parameters is shown in the attached Figure 7 The coating thickness can reach 10-12 microns. The friction coefficient is 0.14 and the wear rate is 9.13×10 -7 mm 3 ·N -1 ·m -1 .
[0122] The above disclosures are only several preferred embodiments of the present invention, which certainly cannot be used to limit the scope of the present invention. Therefore, equivalent changes made according to the claims of the present invention are still within the scope of the present invention.
Claims
1. A method for preparing a wear-resistant coating on a titanium-based surface by micro-arc oxidation, Features: A titanium substrate with a clean and dry surface is taken as the treatment object, the treatment object is taken as the anode, and stainless steel is taken as the cathode. The cathode and the anode are placed in a micro-arc oxidation solution and micro-arc oxidation is performed to prepare a wear-resistant coating on the surface of the titanium substrate.
2. A method for preparing a wear-resistant coating on a titanium-based surface by micro-arc oxidation according to claim 1, Features: The micro-arc oxidation electrolyte comprises phosphoric acid, oxalic acid, hydrogen peroxide, glycerol and additives; in the micro-arc oxidation electrolyte, the concentration of phosphoric acid is 0.1-0.5 mol / L, the concentration of oxalic acid is 0.5-1.5 mol / L, the concentration of hydrogen peroxide is 0.5-1.5 mol / L, and the concentration of glycerol is 0.1-0.2 mol / L; the additive is selected from at least one of 1,2-cyclohexanediaminetetraacetic acid, sulfuric acid, hydrochloric acid, formic acid, nitric acid, and acetic acid; among the additives of the micro-arc oxidation solution, the concentration of any one additive is 0.01-1 mol / L.
3. A method for preparing a wear-resistant coating on a titanium-based surface by micro-arc oxidation according to claim 1, Features: The titanium substrate is cut according to the set size and a small hole is reserved, and then the surface is pretreated to obtain a sample with a clean and dry surface.
4. A method for preparing a wear-resistant coating on a titanium-based surface by micro-arc oxidation according to claim 1, Features: The titanium substrate is clamped in the electrolytic cell by a titanium wire clamp and connected to the positive electrode of the power supply, with a distance of 30-100 mm from the cathode; a micro-arc oxidation electrolyte is provided between the positive electrode and the negative electrode; the cathode can be a stainless steel electrolytic cell; and the titanium substrate is pure titanium or a titanium alloy.
5. The method for preparing a wear-resistant coating on a titanium-based surface by micro-arc oxidation according to claim 1, Features: The power supply mode used for micro-arc oxidation is a constant current to constant voltage mode; the constant current to constant voltage mode is: the current is controlled to be constant current in the early stage, and when the voltage reaches the specified voltage, the constant current mode is changed to the constant voltage mode.
6. A method for preparing a wear-resistant coating on a titanium-based surface by micro-arc oxidation according to claim 1, Features: The micro-arc oxidation electrical parameters include: The forward current is 0.1-2.5A, preferably 1-2A, and more preferably 1.5-2A; The positive voltage is 160-400V, preferably 200-350V, and more preferably 240-310V. When used in industry, 240-260V, 258-280V, 280-305V, etc. can be selected. The negative voltage is 0-15V, preferably 4-11V, and more preferably 5-10V; The frequency is 0-150 Hz, preferably 80-120 Hz, and more preferably 95-105 Hz. The micro-arc oxidation reaction time is 5-20 minutes and the temperature is 20-40°C.
7. A method for preparing a wear-resistant coating on a titanium-based surface by micro-arc oxidation according to claim 2, Features: The electrolyte ratio is: phosphoric acid concentration is 0.25 mol / L, oxalic acid concentration is 0.5 mol / L, glycerol concentration is 0.15 mol / L, hydrogen peroxide concentration is 1.2 mol / L; and additives are 1,2-cyclohexanediaminetetraacetic acid 0.05 mol / L, sulfuric acid 0.5 mol / L, formic acid 0.1 mol / L, acetic acid 0.1 mol / L.
